PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KOMUNIKASI TERHADAP KEPUASAN KERJA KARYAWAN PADA BALI MANDIRA - Wiswananda, Gede Aris; Netra, I Gusti Salit Ketut (E-Jurnal Manajemen; Vol 6 No 12 (2017), 2017)
The purpose of this study was to determine the effect of transformational leadership and communication on employee job satisfaction at Bali Mandira Beach Resort . Data type has been used in this study that are quantitative and qualitative. Data has been used in this study are primary that get directly through fill of questioner by respondents. Population in this study is all of employee in Bali Mandira Beach Resort & Spa Legian at Badung regency by number of 178 people. From the result shows that transformational leadership have positive and significant toward work satisfaction at Bali Mandira Beach Resort & Spa Legian at Badung regency . Comuunication have positive and significant toward work satisfaction at Bali Mandira Beach Resort & Spa Legian at Badun g.